Nicolai Vasilyevich Ivanov: addition to biography of chekist-transport worker - V. P. Vasilevsky; A. V. Sushko (Омский научный вестник: Серия "Общество. История. Современность")
The article deals with the biography reconstruction of the chekist-transport worker (public security officer) N. V. Ivanov. The authors comes to the conclusion that the life and fate of N. V. Ivanov makes it possible to cast doubt to the popular postulate that in 1937 all the «old school checklists» were destroyed by J. V. Stalin. N. V. Ivanov was a communist, distinguished himself in struggle against banditry, approved himself as a good professional in the eyes of the governing body. Thus, N. V. Ivanov secured his career promotion in the Soviet transport security agencies, and received many national honorary awards for his service, successfully surviving mass political repressions